The New RNA-Editing Era – Ethical Considerations. Issue 8 (August 2021) - Gold, Azgad; Levanon, Erez Y.; Eisenberg, Eli
Abstract : The characteristics of RNA editing, including the lower risk compared with genome editing, may loosen the ethical barriers that are currently imposed on genetic engineering, thus opening new possibilities for research, therapy, and human enhancement. We should start considering the future ethical and social implications of this new and promising technology.